Community Nursing Services in England - Bramwell, Donna; Checkland, Kath; Shields, Jolanta; Allen, Pauline (Springer Nature, 2023)
This open access book provides an historical account of the ways in which community nursing services in England have been shaped by policy changes, from the inception of the NHS in 1948 to the present day. Focusing on policies regarding the organisation and provision of community nursing services, it offers an important assessment of how community nursing has evolved under successive governments. The book also provides reflections on how historic policies have influenced the service of today, and how lessons learnt from the past can inform organisation and delivery of current and future community nursing services. It is an important resource for those researching community nursing and health services, as well as practitioners and policy makers.